A decade of stability for wMel Wolbachia in natural Aedes aegypti populations. - Perran A Ross; Katie L Robinson; Qiong Yang; Ashley G Callahan; Thomas L Schmidt; Jason K Axford; Marianne P Coquilleau; Kyran M Staunton; Michael Townsend; Scott A Ritchie; Meng-Jia Lau; Xinyue Gu; et al. (PLoS Pathogens)
Mosquitoes carrying Wolbachia endosymbionts are being released in many countries for arbovirus control. The wMel strain of Wolbachia blocks Aedes-borne virus transmission and can spread throughout mosquito populations by inducing cytoplasmic incompatibility. Aedes aegypti mosquitoes carrying wMel were first released into the field in Cairns, Australia, over a decade ago, and with wider releases have resulted in the near elimination of local dengue transmission. The long-term stability of Wolbachia effects is critical for ongoing disease suppression, requiring tracking of phenotypic and genomic changes in Wolbachia infections following releases. We used a combination of field surveys, phenotypic assessments, and Wolbachia genome sequencing to show that wMel has remained stable in its effects for up to a decade in Australian Ae. aegypti populations. Phenotypic comparisons of wMel-infected and uninfected mosquitoes from near-field and long-term laboratory populations suggest limited changes in the effects of wMel on mosquito fitness. Treating mosquitoes with antibiotics used to cure the wMel infection had limited effects on fitness in the next generation, supporting the use of tetracycline for generating uninfected mosquitoes without off-target effects. wMel has a temporally stable within-host density and continues to induce complete cytoplasmic incompatibility. A comparison of wMel genomes from pre-release (2010) and nine years post-release (2020) populations show few genomic differences and little divergence between release locations, consistent with the lack of phenotypic changes. These results indicate that releases of Wolbachia-infected mosquitoes for population replacement are likely to be effective for many years, but ongoing monitoring remains important to track potential evolutionary changes.